The Effect of Financial Reporting Quality and Capital Structure on Investment Efficiency in Listed Manufacturing Companies - Gusnario Pranata; Fury Khristianty Fitriyah (Universitas Padjadjaran, 2020)
Investment is one of the activities of the company in order to achieve the objectives of the company, which is generally to make a profit. Companies are required to properly plan and use resources to achieve optimum investment and avoid inefficient conditions for investment (overinvestment and underinvestment). This research aims to determine the effect of financial reporting quality and capital structure on investment efficiency in manufacturing companies listed on the Indonesia Stock Exchange. The control variables used in this research are company age, operating cash flow ratio, company size, tangibility, and Altman Z-Score. Secondary data from manufacturing sector companies listed on the Indonesia Stock Exchange during the period 2013 to 2015 are used as the research sample. All variables were analyzed using multiple linear regression analysis. The result of this research indicates that with a 5 percent significance level, financial reporting quality and capital structure variables with company age, operating cash flow ratios, company size, tangibility, and Altman Z-Score as the control variables simultaneously and significantly affect investment efficiency while contributing to the effect of 30.3 percent. Partially, financial reporting quality has a positive and significant effect on investment efficiency, and capital structure has a significant effect on investment efficiency